Fenomena Wisuda PAUD: Motif Pelaku Pendidikan dan Respons Orang Tua di Kota Mataram - Yuyun Ayu Lestari (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
This study was motivated by the limited number of studies on the phenomenon of graduation ceremonies in early childhood education institutions, although this practice has the potential to create economic burdens for families and social pressure. This study aims to analyze various expenses imposed on families as well as the motives of educational actors in implementing early childhood education graduation ceremonies. This study used a qualitative approach with a descriptive case study design. The research participants were parents of students at several early childhood education institutions in Mataram City, West Nusa Tenggara, who were selected using purposive sampling. Data were collected through in-depth interviews based on semi-structured guidelines, visual documentation, and document study, and were then analyzed using the Miles and Saldaña model, which includes data collection, data condensation, data display, and conclusion drawing and verification. The results showed that the implementation of early childhood education graduation ceremonies created financial burdens and social pressure for families, while also reflecting the motives of educational actors in maintaining this practice. This finding is in line with the principle that efficient and relevant educational financing applies not only to academic activities but also to non-academic activities. The conclusion of this study emphasizes that the problems surrounding the implementation of early childhood education graduation ceremonies require clear policies, both from policymakers and from schools. The implications of this study include a theoretical contribution to strengthening the understanding that education can play a role in social reproduction through cultural, economic, and symbolic aspects, as well as practical implications for early childhood education institutions, parents, policymakers, and society in evaluating the benefits of early childhood education graduation ceremonies more proportionally.